Odpowiedzi

2010-03-08T14:55:54+01:00
1) 4x-2+(5x+3)=9x+1 x= -2
9*(-2)+1=-18+1=-17
2) -(y²+5y-6)+(2y²-y)+8= -y²-5y+6+2y²-y+8=y²-6y+14
y= -2
(-2)²-6*(-2)+14=4+12+14=30
3) 5(x²-a+x)+3(x²-2a-3x)= 5x²-5a+5x+3x²-6a-9x=8x²-11a-4x x= -1
[8*(-1)]²-11a-4*(-1)=56-11a+4=60-11a

2010-03-08T14:59:35+01:00
1) 4x-2+(5x+3)= 4*(-2)+(5*(-2)+3)=-8-13=-21
x= -2
2) -(y²+5y-6)+(2y²-y)+8=-((-2)²+(5*(-2)-6)+(2*(-2)²+2)+8=-(4-16)+6+8=-(-12)+14=12+14=26
y= -2
3) 5(x²-a+x)+3(x²-2a-3x)=5((-1)²-a-1)+3((-1)²-2a-3*(-1)=-5(1-a-1)+3(1-2a+3)=-5+5a+5+3-6a+9=12-a
x= -1